Balancing the Space Economy and Sustainability: Legal Frameworks and Policy Initiatives for Responsible Space Activities - Mefteh, Boudour (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
The potential for space exploration to drive economic growth and innovation is immense, but it must be done in a way that ensures the long-term sustainability of outer space. This involves considering the environmental impact of space activities and how to maintain economic benefits over time. This paper addresses the economic opportunities provided by space activities while mentioning the potential risk if space sustainability is not viewed as being as important as the benefits gained from the space mission. This study investigates the regulatory framework of sustainability, which merges legally binding and non-legally binding frameworks. Besides the above, initiatives balancing the space economy and sustainability are discussed.